Frontal brain cavernoma in a 14-year-old boy: differential diagnosis of secondary headache - Nogueira, Eduardo de Almeida Guimarães; Queiroz, Marcos Vinicius de; Saccab, Philipe Rachas; Zanatelli, Marcelo Motta (Headache Medicine, 2020)
Cavernoma consists of a rare type of vascular anomaly that can present with different neurological manifestations. This article reports a case of cavernoma in a 14-year-old boy, whose first symptom was headache